2010
DOI: 10.1111/j.1464-410x.2010.09243.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of phosphodiesterase‐5 inhibitors on Leydig cell secretory function in oligoasthenospermic infertile men: a randomized trial

Abstract: Study Type – Therapy (RCT)
Level of Evidence 1b OBJECTIVE To evaluate the effects of phosphodiesterase‐5 inhibitors (PDE5‐i) on Leydig cell secretory function (LCSF). PATIENTS AND METHODS In all, 75 men with oligoasthenospermia were treated daily for 12 weeks with either vardenafil (23 men, group A), sildenafil (25 men, group B) or l‐carnitine (26 men, group C); a further group of 22 men with oligoasthenospermia (group D) received no treatment. Serum levels of insulin‐like‐3 peptide (INSL3) were evaluated befo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
40
0
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 27 publications
3
40
0
4
Order By: Relevance
“…[26,27] In addition to restoring sexual function, PDE5 inhibitors have also been shown to enhance the Leydig cell secretory function, increasing sperm function and aiding sperm motility. [28] The emerging studies point to the efficacy of combination therapy (testosterone supplementation and PDE5 inhibitor use) over monotherapy in the management of ED, especially in men who have a low testosterone level.…”
Section: Avanafilmentioning
confidence: 99%
“…[26,27] In addition to restoring sexual function, PDE5 inhibitors have also been shown to enhance the Leydig cell secretory function, increasing sperm function and aiding sperm motility. [28] The emerging studies point to the efficacy of combination therapy (testosterone supplementation and PDE5 inhibitor use) over monotherapy in the management of ED, especially in men who have a low testosterone level.…”
Section: Avanafilmentioning
confidence: 99%
“…A few studies have suggested that administration of PDE5 inhibitors and in particular sildenafil and vardenafil in infertile men has either positive effects or lack of effects on the standard parameters of semen analysis (Dimitriadis et al, 2010). Leydig cells express PDE5 (Scipioni et al, 2005).…”
Section: Hydrolysis Of Cgmp and Camp In Leydig Cellsmentioning
confidence: 99%
“…Leydig cells express PDE5 (Scipioni et al, 2005). Dimitriadis et al, (2010) investigated the effects of PDE5 inhibitors on Leydig cellular secretory function and on the standard parameters of semen analysis. The authors evaluated peripheral serum levels of Insl3 in patients with oligoasthenospermia prior to and after PDE5 administration.…”
Section: Hydrolysis Of Cgmp and Camp In Leydig Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…2 7 Trifokale TE-SE. (Adaptiert nach [5])Abb 3. 8 Die mikrochirurgische Varikozelektomie verbessert die Schwangerschaftsrate in der unfruchtbaren Partnerschaft [6] Nach resezierenden viszeralchirurgischen Eingriffen hängt das Wohl der Patienten entscheidend von einer intakten Anastomosenheilung ab.…”
unclassified